2011
DOI: 10.1007/s11104-011-0987-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term removal of wheat straw decreases soil amorphous silica at Broadbalk, Rothamsted

Abstract: Aims Most cereals accumulate Si in their shoots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 31 publications
0
79
1
Order By: Relevance
“…It is shown by a long-term trial conducted at Rothamsted Experimental Station that the annual straw exports from wheat fields reduce the amount of phytolith input to the soil, which decreases the bio-available Si in soils. A significant correlation between Si concentration in straw and yield is also shown 7 . In a long-term trial with rice conducted at four experimental stations located in northern Japan, it was shown that the plant-available Si in the surface soil with continuous rice straw application was 1.25 times higher than without the application 10 .…”
Section: Discussionmentioning
confidence: 72%
“…It is shown by a long-term trial conducted at Rothamsted Experimental Station that the annual straw exports from wheat fields reduce the amount of phytolith input to the soil, which decreases the bio-available Si in soils. A significant correlation between Si concentration in straw and yield is also shown 7 . In a long-term trial with rice conducted at four experimental stations located in northern Japan, it was shown that the plant-available Si in the surface soil with continuous rice straw application was 1.25 times higher than without the application 10 .…”
Section: Discussionmentioning
confidence: 72%
“…In soil, Si compounds mainly present as SiO 2 , about 50-70 % of the soil mass, and in various aluminosilicate forms (Sommer et al, 2006). Although Si is abundant in soil, but most of its sources are not available for plant uptake due to low solubility of Si compounds in soil (Guntzer et al, 2012;Rizwan et al, 2012;Peera et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also Guntzer et al (2012b), in their long-term experiments conducted at Rothamsted, demonstrated that liming significantly increases the amounts of the available forms of silicon in the soil. By comparison, Kim et al (2010) showed that long-term mineral and organic fertilization in the absence of liming did not affect the available silicon content of a sandy soil over a 56-year period.…”
Section: Resultsmentioning
confidence: 99%